EFFECT OF DIFFERENT HERBICIDES ON BIDENS PILOSA AND EUPHORBIA HETEROPHYLLA BIOTYPES RESISTANT TO ALS INHIBITORS - Pereira, Maria Renata Rocha; Marchi, Sidnei; Martins, Dagoberto [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2022)
Select herbicides with different mechanism of action is a satisfactory option for resistant weed control. Then, the present work aimed to study the efficiency of different herbicides and their mixtures on Bidens pilosa (blackjack) and Euphorbia heterophylla (wild poinsettia) biotypes, resistant to ALS herbicides in two development stages. The trials we arranged in a completely randomized design with four replications. The treatments tested were (g a.i/a.e ha-1): imazethapyr at 70 and 140 (WG formulation) + 1.0% Assist; imazethapyr at 57.6 and 72 (SL formulation) + 1.0% Assist; imazapic + imazethapyr at 56 and 70 + 1.0% Assist; glyphosate + imazethapyr (596); saflufenacil + glyphosate at 35 + 720 + 0.5% Dash in tank mix, glyphosate at 720 and, a control without herbicide application. Control efficiency was evaluated, as well as dry matter accumulation at the end of the studies. Plants of both species were more susceptible to herbicides at the early stage of development (2 to 4 leaves). The treatments with saflufenacil + glyphosate, (imazethapyr + glyphosate) and glyphosate promoted the best controls, regardless of the species studied and the application stage. The mixture with saflufenacil provided the highest control speed, and the mixture (imazethapyr + glyphosate) was less efficient among three excellent treatments when applied to plants in the 4-6 leaf stage. The treatments (imazethapyr, in both formulations) and (imazethapyr + imazapic) were ineffective in controlling the studied biotypes, regardless of dose and developmental stage studied.
Keywords: Acetolactate Synthase; Blackjack; Resistance; Wild Poinsettia